Alterações endócrinas e metabólicas em pacientes HIV positivos com lipodistrofia - YAMANO, Ernesto Yoshihiro Seki (Universidade Federal do Pará, 2013)
Lipodystrophy is one of the complications of highly active antiretroviral therapies (HAART). This study evaluates the metabolic and endocrine changing in patients with lipodystrophy. Forty patients were evaluated and classified as lipoatrophy, lipohypertrophy and mixed syndrome. We analyzed insulin resistance for HOMA-IR (Homeostasis Model Assesment Insulin Resistance), fasten glucose and OGTT, urea, creatinine, TSH, Free T4, cortisol, DHEA, ratio cortisol/DHEA, prolactin, testosterone (in male), FSH, LH and estradiol (in female), total cholesterol, LDL-c, HDL-c, uric acid. Anthropometrics measures (Weight, height, body mass index, waist, hip and skin folds thickness), ultrasonographic exams for evaluate hepatic steatosis and measure of bone density. The isolated lipohipertrophy occurred only in female (p<0,05). The mean of age was similar in the groups, without changing in the distribution by age group. Dyslipidemia occurred in all groups after HAART (lipodystrophy mixed, 100%, lipohypertrophy, 80% and lipoatrophy, 70%). Antropometric data showed waist increased in the female with lipohypertrophy (98+ 13,4) and decreased in female with lipoatrophy (76,8 + 6,1). Patients with lipoatrophy have been eutrophic (82,4%) and patients with lipohypertrophy have overweight or obesity (60%). Male was associated with osteoporosis (p < 0,05). We found elevated prevalence of the dyslipidemia (85%) and metabolic syndrome (37,5%) in all groups. The metabolic syndrome was associated with lipohypertrophy. No significant changes were found in the thyroid, cortisol, cortisol/DHEA ratio, testosterone, FSH, LH and prolactina. Conclusions: Female is associated with isolated lipohypertrophy, metabolic syndrome and insulin resistance. Male is related with Osteopenia and osteoporosis. Hepatic steatosis were common, but is not influenced for a type of lipodystrophy. Hormonal changing were unusual events in lipodystrophy.